A method of providing accurate velocity feedback of performance on an instrumented kayak ergometer - Begon, M.; Mourasse, O.; Lacouture, P. (Sports Engineering, 2009)
On a kayak ergometer, an accurate simulation of the athlete-paddle-kayak system kinematics is essential for analysing the relationship between technique and performance. The purpose of this study was to establish a strong relationship between performances on flatwater and performances on an ergometer by means of propulsive force measurement and drag models. Two trials were performed by 12 kayakers in which they were first timed over 250 m of flatwater kayaking (the reference test) and were then asked to perform a trial of the same duration on the ergometer with the same perceived physical exertion. Three techniques for measuring propulsive force and three drag models generated nine combinations, which were all evaluated for their ability to estimate kayak velocity. For each combination, the distance covered by the athlete on the ergometer was simulated. A kayakers` ergometer ranking was based on the average velocity in the ergometer trial. Both distance and ranking were compared to the onwater results. The simulation with the best combination of force measurement and drag model gave an accurate estimate of distance (253 ± 10.5 vs. 250 m) and ranking compared to the reference test.